ANALISIS TRANSFORMASI EKONOMI DAN TEKNOLOGI PADA APLIKASI SIMPERDA DALAM MENINGKATKAN DAYA SAING DI KABUPATEN DELI SERDANG - Royke Bahagia Rizka; Said Bambang Nurcahya (Jurnal Teknologi Komputer dan Informatika, 2022)
The management information system for controlling and evaluating regional development plans (SIMPERDA) is needed to ensure that the economic and digital transformation of regional development in Deli Serdang Regency 2022 can be carried out in accordance with plans and evaluations effectively and efficiently so as to increase regional competitiveness in attracting investment into development capital In the long term, in order to integrate strategic planning and cross-regional apparatus to development priorities and targets, the use of information technology is a method that can combine activity reports for all regional apparatus organizations (OPD) with activity target data entry, physical realization reports and development funds for each organization on a monthly, quarterly basis so that reconciliation can be directly monitored and evaluated by regional heads. In conducting this research the authors immediately created a Discussion Group Forum which involved 43 regional apparatuses and used descriptive analysis, this analysis method is the analysis used by the majority of analysts, to display statistics through mathematical calculations. Its function is to describe the distribution of sample or population data. So that the data will be easy to understand and more informative. Discussion of field results regarding the analysis of the SIMPEDA application which has been carried out within 11 months in 2022 can be used as an evaluation of the performance of the Regional Government of Deli Serdang Regency to further increase regional competitiveness in attracting investment and building for people's prosperity as well as transp